Development of Android-Based Handout Learning Media for Fiqh Subjects at Madrasah Aliyah - Juwi Chahnia; Muhammad Kosim; Rehani Rehani (Murabby: Jurnal Pendidikan Islam, 2024)
This article aims to design the development of teaching materials in the form of Android-based handouts on Fiqh material about Usury, Banks and Insurance for class This research uses the Research and Development (R&D) method. through the 4-D development model (define, design, develop, dissemination), namely a research method that produces learning products starting with needs analysis, product development, product evaluation, product revision and distribution. However, in this research the author limited the use of the method to only the development stage. The results of this research show that in analyzing material on Riba, Banking and Insurance need to be added, such as a discussion of online loans because of the demands of learning outcomes, and also added to the material such as deepening the discussion of the arguments for usury. After the material has been analyzed, it is necessary to design the material that will be included, then systematically handout, and design the research instruments. The instruments used are validation sheets and FDG. The results of the validation show that the suitability aspect of the content presented can be said to be valid with a score of 3.10. Then the language suitability aspect can also be said to be valid with a score of 3.06. And the graphic suitability aspect can also be said to be valid with a total score of 3.02..